The natural history of eczema from birth to adult life: a cohort study. (5th June 2013) - Burr, M.L.; Dunstan, F.D.J.; Hand, S.; Ingram, J.R.; Jones, K.P.
Summary Background Eczema is common in infancy; however, there is little evidence about its natural history to adulthood. Objectives To study the natural history of eczema from birth to young adult life with particular reference to its relation to atopy. Methods A birth cohort of children with atopic family histories was followed for 23 years. Clinical examinations were conducted until the age of 7 years, skin‐prick tests and serum total IgE were recorded in infancy and at ages 7 and 23 years, and questionnaires about eczema symptoms were completed at 15 and 23 years. Results Information was obtained on 497 subjects at birth, 482 at 1 year, 440 at 7 years, 363 at 15 years and 304 at 23 years. Eczema usually remitted from age 1 to 7 years but became more persistent from the age of 15 years, especially in those who were atopic. The prevalence of eczema rose in women from age 15 to 23 years but declined in men. Adults with eczema had higher IgE than those without at 3 months (geometric mean 3·0 vs. 1·7 kU L−1; P = 0·01), 7 years (107·9 vs. 45·2 kU L−1; P = 0·01) and 23 years (123·4 vs. 42·3 kU L−1; P = 0·01), and were more likely to have had positive skin‐prick tests at 1 year of age. Current eczema was associated with raised IgE in infancy and adulthood but not in childhood. Conclusions Predisposed infants and children with eczema usually grow out of the disease, but in adolescence it is more likely to persist. Adult eczema is related to atopy from the age of 3 months.